Trauma sensitive framework for organizations assessment: development and validity of a scale - Rocha, José Carlos (2023)
Background. Trauma-sensitive approaches are usually based on general knowledge of the negative effects of traumatic stress, particularly in high risk contexts or where the impact is higher. However, we still need a robust and complete framework for organizational assessment.Objective. This presentation aims to present an instrument and framework for organizational trauma sensitive care assessment and promotion, with four transversal dimensions, adjustable to multiple contexts.Method. Based on a four dimensions model: training, policies and practices, physical environment and supervision, this team developed a scale firstly applied to residential care and schools. This approach provided a consolidated version composed of 42 Likert items adjusted to most contexts and adaptable to include extra items saturating context-specific topics. This scale was applied to 130 workers from the welfare system in Portugal.Results. Results for mean overall results are 136,3 (SD=30,0) internal consistency provides a Cronbach alpha of 0,96 for the whole scale, ranging from 0,87 to 0,97. The exploratory factor analysis has almost perfect fit with the expected structure, except for the training factor where some items saturated on policies and practices factor. The overall structure explains 58,7% of variance.Conclusions. There is good evidence of both reliability and validity of the scale. This scale will be useful for deep diagnosis of organizations’ needs and to evaluate effects of trauma-sensitive programs and for organizations' trauma sensitive care certification. Another advantage is its adaptability for several contexts like the ongoing efforts in refugees support organizations or health related hospital services.